The Janus Head of T Cell Aging – Autoimmunity and Immunodeficiency - Goronzy, Jorg J.; Li, Guangjin; Yang, Zhen; Weyand, Cornelia M. (Frontiers in Immunology, 2013)
Immune aging is best known for its immune defects that increase susceptibility to infections and reduce adaptive immune responses to vaccination. In parallel, the aged immune system is prone to autoimmune responses and many autoimmune diseases increase in incidence with age or are even preferentially encountered in the elderly. Why an immune system that suboptimal responds to exogenous antigen fails to maintain tolerance to self-antigens appears to be perplexing. In this review, we will discuss age-associated deviations in the immune repertoire and the regulation of signaling pathways that may shed light on this conundrum.